2020
DOI: 10.3233/nre-203131
|View full text |Cite
|
Sign up to set email alerts
|

The clinical correlates of participation levels in people with multiple sclerosis

Abstract: BACKGROUND: Multiple sclerosis (MS) has a huge impact on patients and affects their ability to participate in meaningful activities. OBJECTIVE: To identify motor and non-motor factors that are associated with the participation level in instrumental activities of daily living (IADL), leisure, social and religious activities in people with MS. METHOD: This is a cross-sectional study conducted on 110 individuals with MS. The used outcome measures are: Arabic version of the Activity Card Sort, Berg Balance Scale, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Fatigue is highly debilitating, affects around 80% of PwMS, and is a leading cause of diminished quality of life and reduced social participation 67,68 . Despite its impact, existing interventions to treat fatigue are only modestly to moderately effective for a subset of individuals, making the identification of treatable secondary contributors a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is highly debilitating, affects around 80% of PwMS, and is a leading cause of diminished quality of life and reduced social participation 67,68 . Despite its impact, existing interventions to treat fatigue are only modestly to moderately effective for a subset of individuals, making the identification of treatable secondary contributors a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…MoCA and a score of < 7 on the Instrumental Activities of Daily Living Scale (Table 3) to diagnose dementia based on the published cutoff score from Nasreddine et al 61 Some studies reported data-driven (e.g., regression-based) cutoffs. 45,60,62,63 The participants' age varied considerably across studies ( -The CDR fails to detect frontotemporal dementia.…”
Section: The Unreliable Testing Of Cognitive Abilitiesmentioning
confidence: 99%
“…For instance, Khatib et al 52 applied a score of ≤ 24.5 on MoCA for dementia detection based on receiver operating characteristic curve derived from the study sample, while Assaf et al 51 used a combined score of ≤ 26 on MoCA and a score of < 7 on the Instrumental Activities of Daily Living Scale (Table 3) to diagnose dementia based on the published cutoff score from Nasreddine et al 61 . Some studies reported data‐driven (e.g., regression‐based) cutoffs 45,60,62,63 …”
Section: The Case Of the Mena Regionmentioning
confidence: 99%
“…Thus, these symptoms have an important impact on the ability to participate in meaningful activities with repercussions on individuals and societies ( 2 4 ). Overall, participation is defined as the “involvement in a life situation,” which includes daily activities, leisure, social activities, and work ( 5 , 6 ). Participation is associated with life quality, self-efficacy, and self-esteem and has been proposed as a determinant of health status.…”
Section: Introductionmentioning
confidence: 99%
“…Participation is associated with life quality, self-efficacy, and self-esteem and has been proposed as a determinant of health status. Thus, currently, the rehabilitation process tends to focus on improving the participation level among patients ( 6 ). When a person with MS starts a rehabilitation process, it is essential to identify the needs, based not only on the symptoms but also on the difficulties encountered in daily life.…”
Section: Introductionmentioning
confidence: 99%